2002
DOI: 10.1021/jp015615c
|View full text |Cite
|
Sign up to set email alerts
|

Breathers or Structural Instability in Solid L-Alanine:  a New IR and Inelastic Neutron Scattering Vibrational Spectroscopic Study

Abstract: Incoherent Inelastic Neutron Scattering data and new infrared spectra were acquired in order to examine both the external and internal vibrations in crystalline L-alanine. For the first time we observe a splitting of the NH3 + torsional band below a temperature of approximately 220 K as well as an overtone of this band. The intensity of both of these bands is strongly dependent on temperature. Birefringence and depolarization measurements performed with single crystals reveal a subtle breaking of symmetry arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
73
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 19 publications
10
73
1
Order By: Relevance
“…First, a lattice instability is confirmed in the range 200-230 K, which affects all the low-wavenumber modes. This is in agreement with depolarization measurements, 10 but is surprising because no phase transition is known for this crystal on cooling. 1 -3 A question arises concerning the possible nature of this instability.…”
Section: Discussionsupporting
confidence: 89%
“…First, a lattice instability is confirmed in the range 200-230 K, which affects all the low-wavenumber modes. This is in agreement with depolarization measurements, 10 but is surprising because no phase transition is known for this crystal on cooling. 1 -3 A question arises concerning the possible nature of this instability.…”
Section: Discussionsupporting
confidence: 89%
“…For L-isoleucine crystals, another aliphatic proteic amino acid, the same temperature changes verified in the L-valine experiment (20 -300 K) do not affect the stability of the structure [8]. L-alanine crystal, the smallest chiral aliphatic amino acid, when submitted to the same temperature conditions, seems to maintain the orthorhombic roomtemperature structure, although the existence of a strong dynamic Jahn-Teller effect originated from the NH + 3 chargelattice coupling would explain a previouly misterious lattice instability at ∼ 250 K [9]. Also, recently it was discovered that when L-alanine is fully deuterated, a structural phase transition is observed for temperature lower than 200 K [17].…”
Section: High-temperature Raman Spectramentioning
confidence: 63%
“…For the first three amino acids previous investigations do not shown any structural phase transition under temperature changes [5 -8], although a study involving birrefrigence and light depolarization measurements have shown some symmetry breaking around 220 K for L-alanine [9]. It is also important to state that differently from the temperature change experiments, there is evidence that L-alanine undergoes a structural phase transition at about 2.2 GPa under high pressure conditions [10].…”
Section: Introductionmentioning
confidence: 90%
“…These studies have unveiled interesting and, to some extent, surprising results. Among them we may mention an unusual temperature dependence of the energy of the infrared band related to the torsion of NH 3 + group [1,7], the negative thermal expansion along the c-axis [9], the non-linear temperature dependence of the intensities of Raman modes located at about 42 and 49 cm -1 , which are associated with a dynamic localization of vibrational energy [10], the unusual thermal conductivity [11], the unusual low-temperature symmetry breaking observed by birefrigence [12] as well as NMR experiments [13], but not yet confirmed by XRD [9].…”
Section: Introductionmentioning
confidence: 99%